Keberadaan Kawasan Agropolitan Belajen terhadap Ekonomi Daerah di Kabupaten Enrekang - Haeruddin Haeruddin (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2015)
This type of research used in this research is descriptive qualitative research. The problem of this research are: (1) The public response to the policy of regional development Agropolitan Belajen in Enrekang; and (2) the impact of regional development policies Agropolitan Belajen to the local economy in Enrekang. The research location is in Enrekang South Sulawesi province. Consideration researchers chose these locations is because researchers looked Enrekang as one of the districts in South Sulawesi implementing regional development policy based on agriculture with Agropolitan system. The analysis method used in this research is a model of data analysis techniques Miles and Huberman which consists of data reduction, a data display, and conclusion drawing / verification.The results show the role of government in this matter of government policy in supporting the development of the agricultural sector is very influential, the government can provide the infrastructure agropolitan, provision of economic institutions and the provision of the factors that affect the agricultural sector. So that agricultural productivity Enrekang area from year to year has increased and contributes to regional economic terhada. Sustainability agropolitan area in the district Enrekang can provide benefits to the community, especially the increase in production and incomes of farmers